2020
DOI: 10.37358/mp.20.1.5337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of DCPD and ENB Healing Systems in Glass Fibre Composites

Abstract: The present paper is focused on evaluating the mechanical characterization of dicyclopentadiene (DCPD) and 5-ethylidene-2-norbornene (ENB) healing systems synthetized by in-situ polymerisation. Both healing systems were embedded in glass fibre reinforced polymer (GFRP) composite and subjected to three-point bending test regime. Microstructural and FT-IR analysis showed the formation of microcapsules and a successful integration in the composite material. To observe the influence of temperature variation, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Chemical substances used in the production of melamine-urea-formaldehyde (MUF) microcapsules with embedded 5-ethylidene-2-norbornene (ENB). Microcapsules from the same batch, synthesized by in situ polymerization, were used, as presented in [33]. The fabrication of MUF-ENB microcapsules required four solutions to be prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical substances used in the production of melamine-urea-formaldehyde (MUF) microcapsules with embedded 5-ethylidene-2-norbornene (ENB). Microcapsules from the same batch, synthesized by in situ polymerization, were used, as presented in [33]. The fabrication of MUF-ENB microcapsules required four solutions to be prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Microcapsules from the same batch, synthesized by in situ polymerization, were used, as presented in [33]. In a 600 mL tall-form glass beaker, two solutions were initially prepared: a solution containing 150 mL distilled water, 7 g urea, 0.5 g resorcinol, and 0.5 g ammonium chloride, and a solution containing 100 mL co-polymer 5 wt % maleic anhydride.…”
Section: Synthesis Of Puf-dcpd Microcapsulesmentioning
confidence: 99%
“…As the research progresses, researchers have developed more efficient healing agents based on ROMP reactions. Vintil a et al 59 embedded microcapsules with 5-ethylene-2-norbornene (ENB) in glass fiber reinforcement polymer (GFRP) composites and compared them F I G U R E 4 Schematic of the healing agent delivery mechanism utilized by the mendable epoxy resins containing EMAA particles. 55 F I G U R E 5 (A) Insertion of mesh in the agitator.…”
Section: Microcapsulesmentioning
confidence: 99%
“…As the research progresses, researchers have developed more efficient healing agents based on ROMP reactions. Vintilă et al 59 embedded microcapsules with 5‐ethylene‐2‐norbornene (ENB) in glass fiber reinforcement polymer (GFRP) composites and compared them with the DCPD counterpart. The results showed that the urea‐formaldehyde microcapsules prepared by the same method were smaller in diameter for ENB (30–100 μm) than for DCPD (100–250 μm).…”
Section: Extrinsic Self‐healing Compositesmentioning
confidence: 99%
“…[16] studied the low velocity impact properties of different hybrid fibre reinforced composite laminates and it was concluded that the best performances were obtained for laminates that have glass fibre external layers. Beside these studies, many researches were conducted in the last decade regarding hybrid fibre reinforced polymeric composites [7,17,18], 3D printed fibre reinforced composites [19][20][21], and even self-healing fibre reinforced polymeric composites [22,23].…”
Section: Introductionmentioning
confidence: 99%